Customer Engagement, Digital Promotion, dan Influencer Credibility Sebagai Faktor yang Mempengaruhi Purchase Decision dan Customer Loyalty Produk Skincare pada Pembelian di Social Commerce - Maulidyah Ahza; Usep Suhud; Meta Bara Berutu (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study aims to analyze the influence of customer engagement, digital promotion, and influencer credibility on purchase decisions and customer loyalty in the context of purchasing local skincare products, Somethinc, through the social commerce platform TikTok Shop. This study used a quantitative approach with a survey method through a questionnaire distributed online to respondents residing in Jakarta and having purchased Somethinc products on TikTok Shop at least three times in the past six months. The sampling technique used was purposive sampling, with a sample size of 270 respondents. Data were analyzed using Structural Equation Modeling (SEM) based on SmartPLS software. The results of the study indicate that: 1) customer engagement has a positive but insignificant effect on purchase decisions, 2) customer engagement has a positive and significant effect on customer loyalty, 3) digital promotion has a positive and significant effect on purchase decisions, 4) digital promotion has a positive and significant effect on customer loyalty, 5) influencer credibility has a positive and significant effect on purchase decisions, 6) influencer credibility has a positive and significant effect on customer loyalty, and 7) purchase decisions have a positive and significant effect on customer loyalty. This study provides theoretical implications for the development of digital marketing science as well as practical recommendations for businesses, particularly local skincare brands like Somethinc, in developing effective marketing strategies in the era of social commerce.